Positive plate and preparation method thereof, battery, battery pack and electric equipment

By layering the inorganic interface film composed of transition metal phosphate and lithium carbonate on the surface of the positive electrode active material, the problem of poor stability of traditional CEI films is solved, and the long cycle stability and service life of the battery are significantly improved.

CN119786510APending Publication Date: 2025-04-08BYD CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411338182.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The solid interface film (CEI film) on the surface of traditional positive electrode materials has poor stability, which leads to volume changes during the charging and discharging of the battery, and the CEI film ruptures or decomposition, which in turn affects the cycling stability of the battery.

Method used

A positive electrode sheet including a first inorganic interface film and a second inorganic interface film is adopted. The first inorganic interface film is composed of transition metal phosphate, and the second inorganic interface film is composed of lithium carbonate. These interface films are sequentially laminated and coated on the surface of the positive electrode active material to form an interface structure with high mechanical strength and chemical stability.

Benefits of technology

It effectively improves the long cycle stability of the battery, prevents direct contact between the electrolyte and the positive electrode material, reduces the occurrence of side reactions, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786510A_ABST
    Figure CN119786510A_ABST
Patent Text Reader

Abstract

The invention provides a positive plate and a preparation method thereof, a battery, a battery pack and electric equipment, the positive plate comprises a current collector and an active layer of at least one functional surface of the current collector, the active layer comprises a positive active material, at least part of the surface of the positive electrode active material is sequentially coated with a first inorganic interfacial film and a second inorganic interfacial film in a laminated manner, and the first inorganic interfacial film comprises transition metal phosphate; the second inorganic interfacial film comprises lithium carbonate. The positive plate provided by the invention can continuously block the contact between a positive electrode material and an electrolyte during long-time cycle use of the battery, so that the long-cycle stability of the battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a preparation method thereof, a battery, a battery pack, and an electrical device. Background Art

[0002] Due to the increasing demand for fast-charging and high-energy-density batteries in the consumer market, some research on the modification of high-energy-density battery cells has gradually matured. However, as the battery energy density and fast-charging performance increase, the battery cycle performance will decrease to varying degrees.

[0003] The stability of the interface between electrode materials and electrolytes is the key to achieving stable cycling of high specific energy batteries. Among them, the solid interface film formed on the surface of electrode materials is considered to be an important reason affecting the stability of the interface between electrode materials and electrolytes. For example, the solid interface film (CEI film) on the surface of the positive electrode material can prevent direct contact between the electrolyte and the positive electrode material, thereby reducing the occurrence of side reactions.

[0004] The current CEI membrane has poor stability. The positive electrode material undergoes volume changes during the charge and discharge process. The CEI membrane is subjected to mechanical stress and will break or decompose. Therefore, providing a CEI membrane with high stability is of great significance to alleviate the decline in battery cycle stability. Summary of the invention

[0005] The present invention provides a positive electrode sheet, which includes a first inorganic interface film and a second inorganic interface film, and can effectively alleviate the problem of decreased long-cycle stability of a battery due to poor stability of a traditional CEI film.

[0006] The present invention also provides a method for preparing the positive electrode sheet, which can be used to prepare the positive electrode sheet, is simple to operate, and is energy-saving and environmentally friendly.

[0007] The present invention also provides a battery comprising the positive electrode sheet, and the battery has excellent cycle stability.

[0008] The present invention also provides a battery pack comprising the battery, which has the advantages of good stability and long cycle life.

[0009] The present invention also provides an electrical device. Since the electrical device comprises the battery or battery pack, the service life of the electrical device is relatively long.

[0010] In detail, in the first aspect, the present invention provides a positive electrode sheet, including a current collector and an active layer on at least one functional surface of the current collector, the active layer including a positive electrode active material, at least a portion of the surface of the positive electrode active material being sequentially stacked and coated with a first inorganic interface film and a second inorganic interface film, the first inorganic interface film including a transition metal phosphate; the second inorganic interface film including lithium carbonate.

[0011] Furthermore, the total thickness of the first inorganic interface film and the second inorganic interface film is f, and f satisfies: 10 nm≤f≤100 nm.

[0012] Furthermore, the thickness of the second inorganic interface film is 2nm-60nm.

[0013] Further, the molar ratio of the lithium carbonate to the transition metal phosphate is 0.1 to 1:1;

[0014] and / or, in the transition metal phosphate, the molar ratio of metal ion to phosphate is 1:1;

[0015] And / or, the mass ratio of the lithium carbonate to the positive electrode active material is 0.05wt%-0.5wt%.

[0016] Furthermore, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese phosphate, lithium iron phosphate, and lithium manganese iron phosphate.

[0017] Furthermore, the transition metal phosphate is at least one of iron phosphate, cobalt phosphate, manganese phosphate, nickel phosphate and aluminum phosphate.

[0018] Furthermore, the positive electrode sheet is prepared by a method comprising the following steps:

[0019] An electrode slurry including a positive electrode active material is coated on at least one functional surface of a current collector, and is dried and rolled to form a precursor; the precursor is placed in a sealed container containing a mixed atmosphere, and reacts for a period of time under a pressure of 0.1-0.3Mpa to obtain the positive electrode sheet; wherein, by volume, the mixed atmosphere includes water, carbon dioxide and oxygen in a molar ratio of 1-1.5:1-1.5:1-1.5.

[0020] In a second aspect, the present invention provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:

[0021] An electrode slurry including a positive electrode active material is coated on at least one functional surface of a current collector, dried and rolled to form a precursor, and the precursor is placed in a closed container containing a mixed atmosphere and reacted for a period of time under a pressure of 0.1-0.3Mpa to obtain the positive electrode sheet; wherein, by volume, the mixed atmosphere includes water, carbon dioxide and oxygen in a molar ratio of 1-1.5:1-1.5:1-1.5.

[0022] Furthermore, the internal temperature of the sealed container is 25°C-60°C.

[0023] In a third aspect, the present invention provides a battery comprising the positive electrode sheet of the first aspect.

[0024] In a fourth aspect, the present invention provides a battery pack comprising the battery described in the third aspect.

[0025] In a fifth aspect, the present invention provides an electrical device, comprising the battery described in the third aspect or the battery pack described in the fourth aspect.

[0026] The positive electrode sheet provided by the present invention comprises a first inorganic interface film and a second inorganic interface film of a specific composition, which have higher mechanical strength, hardness and better chemical stability than traditional organic interface films. Therefore, during long-term cycle use of the battery, the contact between the positive electrode material and the electrolyte can be continuously avoided, thereby effectively improving the long-cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 This is an infrared characterization image of the active layer of the positive electrode sheet of Example 1 of the present invention;

[0029] Figure 2 This is an infrared characterization picture of the active layer of the positive electrode sheet of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In a first aspect, the present invention provides a positive electrode sheet, comprising a current collector and an active layer on at least one functional surface of the current collector, wherein the active layer comprises a positive electrode active material, and at least a portion of the surface of the positive electrode active material is sequentially stacked and coated with a first inorganic interface film and a second inorganic interface film, wherein the first inorganic interface film comprises a transition metal phosphate; and the second inorganic interface film comprises lithium carbonate.

[0032] In the present invention, by sequentially stacking and coating the first inorganic interface film and the second inorganic interface film on at least part of the surface of the positive electrode active material, direct contact between the electrolyte and the positive electrode material can be prevented, and the occurrence of side reactions can be reduced. Moreover, compared with traditional organic interface films, the first inorganic interface film and the second inorganic interface film have higher mechanical strength and better chemical stability. This stability characteristic, combined with the specific inorganic components of the first inorganic interface film and the second inorganic interface film, can effectively improve the long-cycle stability of the battery. In detail, the second inorganic interface film includes lithium carbonate that is ion-conductive and electronically insulating, which can ensure that lithium ions can pass smoothly while electrons are blocked, thereby preventing electrons from being conducted from the positive electrode material to the electrolyte, reducing the occurrence of unnecessary side reactions. In addition, the first inorganic interface film is provided between the positive electrode active material and the second inorganic interface film, which can further increase the lithium ion conduction channel, reduce the resistance to lithium ion transmission, and improve the transmission efficiency of lithium ions, thereby cooperating with the second inorganic interface film to achieve long-term stable cycle of the battery.

[0033] In some embodiments, the presence of the lithium carbonate can be qualitatively characterized by FT-IR, and optionally, the content of lithium carbonate can be quantitatively tested by alkaline titration; the presence of the transition metal phosphate can be obtained by quantitative calculation of each lithium salt.

[0034] It should be noted that the present invention does not specifically limit whether the second inorganic interface film is stacked with other organic interface films on the surface away from the positive electrode active material. In some embodiments, the second inorganic interface film also includes an organic interface film on at least part of the surface away from the positive electrode active material.

[0035] The material of the current collector is not specifically limited in the present invention. For example, the current collector may be selected from any one or more of copper foil, titanium foil, tin foil, chromium foil and composite foils of the above metals.

[0036] In order to improve the energy density of the battery, preferably, the active layers are sequentially arranged on two functional surfaces of the current collector.

[0037] Among them, a thinner inorganic interface membrane has a lower ion conduction impedance, but may be insufficient in electronic insulation and mechanical stability. A thicker inorganic interface membrane has better electronic insulation and mechanical stability, but may increase the ion conduction impedance of the positive electrode sheet, affecting the capacity and efficiency of the battery. Therefore, in a preferred embodiment, the total thickness of the first inorganic interface membrane and the second inorganic interface membrane is f, and f satisfies: 10nm≤f≤100nm.

[0038] Exemplarily, f is 10nm, 15nm, 17nm, 20nm, 25nm, 27nm, 3nm, 32nm, 35nm, 37nm, 40nm, 45nm, 47nm, 50nm, 52nm, 55nm, 57nm, 60nm, 70nm, 80nm, 90nm, 95nm, etc.

[0039] The second inorganic interface film is the main structure that isolates the direct contact between the electrolyte and the positive electrode material. Therefore, in order to further ensure the cycle stability and ion transfer rate of the battery, in a specific embodiment, the thickness of the second inorganic interface film is 2nm-60nm.

[0040] Exemplarily, the thickness of the second inorganic interface film is 2nm, 5nm, 8nm, 10nm, 15nm, 17nm, 20nm, 25nm, 27nm, 3nm, 32nm, 35nm, 37nm, 40nm, 45nm, 47nm, 50nm, 52nm, 55nm, 57nm, 60nm, etc. In another specific embodiment, the molar ratio of the lithium carbonate to the transition metal phosphate is 0.2-1;

[0041] and / or, in the transition metal phosphate, the molar ratio of metal ion to phosphate is 1:1;

[0042] And / or, the mass ratio of the lithium carbonate to the positive electrode active material is 0.05wt%-0.5wt%.

[0043] Among them, the molar ratio of the lithium carbonate and the transition metal phosphate can better balance the cycle stability and ion transfer rate of the battery within the scope of the above embodiment. Further, the mass ratio of the lithium carbonate to the positive electrode active material can reflect the coating amount of the lithium carbonate. If the mass ratio of the lithium carbonate to the positive electrode active material is too high, the coating amount of the lithium carbonate is too large, which affects the rate performance of the battery. If the mass ratio of the lithium carbonate to the positive electrode active material is too low, the coating amount of the lithium carbonate is too small, and the cycle stability of the battery cannot be guaranteed.

[0044] It can be understood that the mass ratio of the lithium carbonate to the positive electrode active material=lithium carbonate / positive electrode active material×100%.

[0045] In a specific embodiment, the second inorganic interface film further includes at least one of lithium bicarbonate, lithium oxide, and lithium hydroxide.

[0046] In a specific embodiment, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese phosphate, lithium iron phosphate, and lithium manganese iron phosphate;

[0047] And / or, the transition metal phosphate is at least one of iron phosphate, cobalt phosphate, manganese phosphate, nickel phosphate, and aluminum phosphate.

[0048] Among them, when the positive electrode active material includes lithium manganese iron phosphate, the first inorganic interface film and the second inorganic interface film can also effectively reduce the probability of manganese dissolution of the positive electrode active material, thereby avoiding the problem of continuous decline in battery life due to manganese dissolution.

[0049] For example, the positive electrode active material lithium manganese oxide can be selected from LiMnO2 and LiMn2O4; the positive electrode active material lithium nickel cobalt manganese oxide can be selected from LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 one or more; the molecular formula of the above-mentioned positive electrode active material lithium manganese iron phosphate is LiFe 1-x- y Mn x M y PO4, wherein 0≤y<1, x+y<1, M is at least one of Mg, Co, Ni, Cr, Zn, Cu, V, Ti, Zr, and Nb; the molecular formula of the positive electrode active material lithium iron phosphate is LiFe 1-y N y PO4, wherein 0≤y<1, and N is at least one of Mg, Co, Ni, Cr, Zn, Cu, V, Ti, Zr, and Nb.

[0050] Preferably, the transition metal phosphate is iron phosphate.

[0051] In some embodiments, the active layer comprises, by weight percentage, 94%-97% of positive electrode active material, 1%-2.5% of conductive agent, 1.2%-2.5% of binder, and 0.5%-1.5% of dispersant.

[0052] Exemplarily, the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersant can be selected from at least one of sodium carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium dodecyl sulfate.

[0053] As for the particle size distribution of the above-mentioned positive electrode active material, the present invention does not make any specific limitation. For example, the D50 of the above-mentioned positive electrode active material can be 5-16μm, including but not limited to 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.; D99 can be 14-30μm, including but not limited to 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, etc.; D10 can be 2-10μm, including but not limited to 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, etc.

[0054] The thickness, surface density and thickness of the active layer of the positive electrode sheet are not specifically limited in the present invention. However, in order to balance the battery capacity, cycle life and energy density, in a specific embodiment, the thickness of the positive electrode sheet is 40-120 μm, including but not limited to: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, etc.; the surface density of the positive electrode sheet is 3-10 mg / cm 2 , including but not limited to: 3.5mg / cm 2 , 4mg / cm 2 , 4.5mg / cm 2 , 5mg / cm 2 , 5.5mg / cm 2 , 6mg / cm 2 、6.5mg / cm 2 , 7mg / cm 2 、7.5mg / cm 2 , 8mg / cm 2 、8.5mg / cm 2 , 9mg / cm 2 、9.5mg / cm 2etc.; the thickness of the active layer is 20-60 μm, specifically including but not limited to: 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, etc.

[0055] In one specific embodiment, the positive electrode sheet is prepared by a method comprising the following steps:

[0056] An electrode slurry including a positive electrode active material is coated on at least one functional surface of a current collector, and is dried and rolled to form a precursor; the precursor is placed in a sealed container containing a mixed atmosphere, and reacts for a period of time under a pressure of 0.1-0.3Mpa to obtain the positive electrode sheet; wherein, by volume, the mixed atmosphere includes water, carbon dioxide and oxygen in a molar ratio of 1-1.5:1-1.5:1-1.5.

[0057] In the above preparation method, the precursor can be understood as a positive electrode sheet without forming the first inorganic interface film and the second inorganic interface film. After the precursor is placed in a sealed container containing a mixed atmosphere, oxygen converts metal ions such as Fe 2+ Oxidation: Carbon dioxide and water provide an acidic environment for oxygen, which increases the oxidizing ability of oxygen and makes metal ions more easily oxidized. At the same time, lithium ions in the positive electrode material are leached out to form lithium hydroxide (see formula 1). Lithium hydroxide reacts with carbon dioxide to produce lithium carbonate (see formula 1). Taking lithium iron phosphate as the positive electrode active material as an example, the positive electrode active material undergoes the following chemical reactions:

[0058] 4LiFePO4 + O2 + 2H2O→4LiOH + 4FePO4 Formula 1,

[0059] 2LiOH+CO2→Li2CO3+H2O Formula 2.

[0060] In a second aspect, the present invention provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:

[0061] An electrode slurry including a positive electrode active material is coated on at least one functional surface of a current collector, dried and rolled to form a precursor, and the precursor is placed in a closed container containing a mixed atmosphere and reacted for a period of time under a pressure of 0.1-0.3Mpa to obtain the positive electrode sheet; wherein, by volume, the mixed atmosphere includes water, carbon dioxide and oxygen in a molar ratio of 1-1.5:1-1.5:1-1.5.

[0062] Among them, the formation process of the traditional positive electrode CEI film mainly includes adding some specific film-forming additives to the electrolyte or promoting the formation of the CEI film through room temperature / low temperature high current charging and discharging steps, but the above existing processes cannot control the content of inorganic components, and the preparation method provided by the present invention can form a first inorganic interface film and a second inorganic interface film including pure inorganic components. In detail, in the above preparation method, the positive electrode precursor without the first inorganic interface film and the second inorganic interface film is placed in a sealed container containing a mixed atmosphere, and oxygen converts the metal ions of the positive electrode active material such as Fe 2+ Oxidation: Carbon dioxide and water provide an acidic environment for oxygen, which increases the oxidizing ability of oxygen and makes metal ions more easily oxidized. At this time, lithium ions in the positive electrode material are leached to form lithium hydroxide and iron phosphate (see chemical formula 1). Lithium hydroxide reacts with carbon dioxide to produce lithium carbonate (see chemical formula 2). Taking lithium iron phosphate as the positive electrode active material as an example, the positive electrode active material mainly undergoes the following chemical reactions:

[0063] 4LiFePO4+O2+2H2O→4LiOH+4FePO4 Chemical formula 1,

[0064] 2LiOH+CO2→Li2CO3+H2O Chemical formula 2.

[0065] In some embodiments, the following side reactions may also be included (see Chemical Formula 3-4):

[0066] Li2CO3+H2O+CO2→LiHCO3 chemical formula 3.

[0067] The internal temperature of the sealed container affects the formation rate of the first inorganic interface film and the second inorganic interface film. In a specific embodiment, the internal temperature of the sealed container is 25°C-60°C.

[0068] The reaction time can be adjusted according to the required thickness of the first inorganic interface film and the second inorganic interface film. For example, the reaction time is 1 hour to 72 hours.

[0069] In some embodiments, the positive electrode sheet precursor may be assembled into a core first, and the core is regarded as the above-mentioned closed container. Then, the preparation of the positive electrode sheet specifically includes the following process:

[0070] Including the pole core of the precursor, at room temperature, open the injection hole, inject a certain amount of mixed gas, seal the injection hole with a rubber plug, after a period of reaction, open the rubber plug, extract and recover the excess gas, and the pole core can flow downward according to the normal process.

[0071] In a third aspect, the present invention provides a battery comprising the positive electrode sheet of the first aspect.

[0072] Illustratively, the battery of the present invention includes a negative electrode sheet, the positive electrode sheet and an electrolyte.

[0073] Exemplarily, the above-mentioned negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder, the negative electrode active material includes one or more of graphite, hard carbon, soft carbon, silicon-based negative electrode, titanium-based material, nitride, tinide, and metallic lithium, the negative electrode current collector can be a conventional negative electrode current collector in the art, for example, including copper foil, etc., the mass fraction of the negative electrode active material in the negative electrode active layer is 92%-98%, the mass fraction of the binder is 0.5%-3%, and the mass fraction of the conductive agent is 0.5%-2.5%.

[0074] The battery of the present invention can be manufactured according to conventional methods in the art, such as stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, assembling the battery cell through a winding process or a stacking process, and then packaging and baking, injecting the electrolyte, and then hot pressing and other processes to obtain the battery.

[0075] Exemplarily, the battery may further include a diaphragm. The present invention does not particularly limit the material of the diaphragm, and any known porous structure diaphragm with electrochemical stability and chemical stability may be selected, for example, it may be at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The diaphragm may be single-layer or multi-layer.

[0076] The present invention does not specifically limit the above-mentioned electrolyte, for example, an electrolyte including an organic solvent and an electrolyte salt is selected. Among them, the organic solvent is used as a medium for transmitting ions in the electrochemical reaction, and can be an organic solvent for battery electrolyte known in the art, such as: one or more of fluorinated carbonates, fluorinated carboxylates, non-fluorinated carbonates, fluorinated carbonates, non-fluorinated carboxylates, fluorinated carboxylates, fluorinated carboxylates, fluorinated ethers, non-fluorinated ethers, and tetrahydrofuran; the electrolyte salt is used as a source of ions, and can be an electrolyte salt for battery electrolyte known in the art, such as: one or more of lithium hexafluorophosphate, bistrifluoromethylsulfonyl imide, and bis(fluorosulfonyl)imide lithium.

[0077] In a fourth aspect, the present invention provides a battery pack comprising the battery described in the third aspect.

[0078] In a fifth aspect, the present invention provides an electrical device, comprising the battery described in the third aspect or the battery pack described in the fourth aspect.

[0079] It should be noted that the above-mentioned electrical equipment can be any conventional equipment that requires electricity, for example, including but not limited to computers, electric cars, air conditioners, refrigerators, washing machines, microwave ovens, printers, fax machines, etc.

[0080] The technical scheme of the present invention is further illustrated below in conjunction with specific examples. All parts, percentages and ratios described in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.

[0081] Example 1

[0082] This example provides a positive electrode sheet and a core, the positive electrode sheet includes a current collector and an active layer on at least one functional surface of the current collector, the active layer includes a positive electrode active material: lithium iron phosphate, at least part of the surface of the positive electrode active material is sequentially laminated and coated with a first inorganic interface film and a second inorganic interface film, the first inorganic interface film includes iron phosphate; the second inorganic interface film includes lithium carbonate;

[0083] The total thickness of the first inorganic interface film and the second inorganic interface film is 75 nm;

[0084] The thickness of the second inorganic interface film is 40 nm;

[0085] The molar ratio of the lithium carbonate to the iron phosphate is 1:1;

[0086] The mass ratio of the lithium carbonate to the lithium iron phosphate is 0.35 wt %.

[0087] The preparation method comprises the following steps:

[0088] 1) Preparation of precursor: The positive electrode active material lithium iron phosphate, the conductive agent (carbon black), and the binder (PVDF) are mixed evenly in N-methylpyrrolidone NMP solvent, wherein the mass ratio of the positive electrode active material, the conductive agent, and the binder is 90:5:5 respectively, and the positive electrode slurry is coated on the surface of the current collector aluminum foil by common extrusion spraying, gravure printing, etc., and the electrode sheet is rolled after drying to obtain the positive electrode sheet;

[0089] 2) Preparation of the electrode core: The positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence, the stacked electrode core is placed in the battery casing, and the cover plate is welded to complete the production of the electrode core.

[0090] 3) Forming an interface film: at room temperature, open the injection hole of the pole core, inject a mixed gas, seal the injection hole with a rubber plug, place the gas-injected pole core at 25°C for 72 hours, then open the rubber plug, remove excess gas and recover it; wherein the mixed gas includes water, carbon dioxide and oxygen in a molar ratio of 1:1:1.

[0091] Example 2

[0092] This example provides a positive electrode sheet and a core, which are basically the same as those in Example 1, and the preparation method thereof comprises the following steps: 1) obtaining a positive electrode sheet by using the precursor preparation process in Example 1;

[0093] 2) placing the positive electrode sheet in a sealed container with an air inlet and an air outlet, introducing / exhausting the mixed gas into the container twice, with the amount of gas each time being based on the volume of the container, replacing the residual air in the container, introducing the mixed gas consistent with that in Example 1 again, and leaving it at room temperature for 72 hours to obtain a positive electrode sheet;

[0094] 3) Prepare the pole core in the same manner as step 2) of Example 1.

[0095] Example 3

[0096] This example provides a positive electrode sheet and a core. The positive electrode sheet is basically the same as that in Example 1, and the only difference is that the total thickness of the first inorganic interface film and the second inorganic interface film is 45 nm.

[0097] The thickness of the second inorganic interface film is 20 nm;

[0098] The molar ratio of the lithium carbonate to the iron phosphate is 1:1;

[0099] The mass ratio of the lithium carbonate to the lithium iron phosphate is 0.2 wt %.

[0100] The preparation method is basically the same as that of Example 1, with the only difference being that the gas-injected electrode core is left at 25° C. for 30 hours.

[0101] Example 4

[0102] This example provides a positive electrode sheet and a core, which are basically the same as those in Example 1, except that the total thickness of the first inorganic interface film and the second inorganic interface film is 65 nm;

[0103] The thickness of the second inorganic interface film is 30 nm;

[0104] The molar ratio of the lithium carbonate to the iron phosphate is 1:1;

[0105] The mass ratio of the lithium carbonate to the lithium iron phosphate is 0.3 wt %.

[0106] The preparation method is basically the same as that of Example 1, with the only difference being that the gas-injected electrode core is left at 25° C. for 50 hours.

[0107] Example 5

[0108] This example provides a positive electrode sheet and a core, which are basically the same as those in Example 1, except that the positive electrode active material is lithium manganese iron phosphate LiFe 1-x-y Mn x My PO4, M is Al, y=0.002, x=0.048.

[0109] Example 6

[0110] This example provides a positive electrode sheet and a core, which are basically the same as those in Example 1, except that the positive electrode active material is doped lithium iron phosphate LiFe 1-y N y PO4, N is Mg, y=0.005.

[0111] Comparative Example 1

[0112] This example provides a positive electrode sheet and a core, which are basically the same as those in Example 1, except that the first inorganic interface film and the second inorganic interface film are not provided on the surface of the positive electrode active material.

[0113] The preparation method thereof is different from that of Example 1 in that there is no water in the mixed gas.

[0114] Comparative Example 2

[0115] This example provides a positive electrode sheet and a core, which are basically the same as those in Example 1, except that the first inorganic interface film and the second inorganic interface film are not provided on the surface of the positive electrode active material.

[0116] The preparation method thereof is different from that of Example 1 in that there is no carbon dioxide in the mixed gas.

[0117] Comparative Example 3

[0118] This example provides a positive electrode sheet and a core, which are basically the same as those in Example 1, except that the first inorganic interface film and the second inorganic interface film are not provided on the surface of the positive electrode active material.

[0119] The preparation method thereof refers to the preparation of the precursor in Example 1.

[0120] Test Case

[0121] Test 1: Positive electrode infrared test

[0122] The positive electrodes of different embodiments and comparative examples were taken and tested for infrared after baking and drying. The results of embodiment 1 and comparative example 3 were as follows: Figure 1 and 2 shown.

[0123] contrast Figure 1 and Figure 2 It can be seen that the infrared spectrum of the positive electrode of Comparative Example 3 only has the characteristic absorption peak of LiFePO4 at 800-1100cm -1 , in the embodiment at 1400-1600cm -1In the region, there is an obvious characteristic peak of lithium carbonate, indicating that the positive electrode sheet of Example 1 successfully forms a second inorganic interface film.

[0124] Test 2: Battery internal resistance before and after cycling

[0125] Test method: The pole core of each embodiment and comparative example was vacuum baked at 85°C for 24h, injected with an electrolyte containing 1mol / L LiPF6, wherein the solvent in the electrolyte was ethylene carbonate and ethyl methyl carbonate in a mass ratio of 3:7, and after 0.02C charging formation, a 25°C, 1C charge and discharge cycle test was performed with a voltage range of 2.0-3.8V. After the battery core had been cycled for a certain period of time, the battery was removed from the charge and discharge cabinet, and a DC internal resistance meter was used to connect the positive and negative electrodes of the battery and read the test internal resistance value. The test results are shown in Table 1.

[0126] Table 1. Battery internal resistance in control experiment and examples

[0127]

[0128] As can be seen from Table 1, in the pole cores assembled in the comparative example, the internal resistance of the batteries showed different growth rates, while in the pole cores of the embodiments in which the first inorganic interface membrane and the second inorganic interface membrane were constructed, the positive electrode side reactions were significantly reduced, and the internal resistance of the batteries basically tended to be stable during the cycle.

[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode sheet, comprising a current collector and an active layer on at least one functional surface of the current collector, wherein the active layer comprises a positive electrode active material, characterized in that: At least a portion of the surface of the positive electrode active material is sequentially laminated and coated with a first inorganic interface film and a second inorganic interface film, wherein the first inorganic interface film includes a transition metal phosphate; and the second inorganic interface film includes lithium carbonate.

2. The positive electrode sheet according to claim 1, characterized in that: The total thickness of the first inorganic interface film and the second inorganic interface film is f, and f satisfies: 10 nm≤f≤100 nm.

3. The positive electrode sheet according to claim 2, characterized in that: The thickness of the second inorganic interface film is 2nm-60nm.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The molar ratio of the lithium carbonate to the transition metal phosphate is 0.1 to 1:1; and / or, in the transition metal phosphate, the molar ratio of metal ion to phosphate is 1:1; And / or, the mass ratio of the lithium carbonate to the positive electrode active material is 0.05-0.5wt%.

5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese phosphate, lithium iron phosphate, and lithium manganese iron phosphate.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The transition metal phosphate is at least one of iron phosphate, cobalt phosphate, manganese phosphate, nickel phosphate and aluminum phosphate.

7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The positive electrode sheet is prepared by a method comprising the following steps: An electrode slurry including a positive electrode active material is coated on at least one functional surface of a current collector, and is dried and rolled to form a precursor; the precursor is placed in a sealed container containing a mixed atmosphere, and reacts for a period of time under a pressure of 0.1-0.3Mpa to obtain the positive electrode sheet; wherein, by volume, the mixed atmosphere includes water, carbon dioxide and oxygen in a molar ratio of 1-1.5:1-1.5:1-1.

5.

8. A method for preparing a positive electrode sheet according to any one of claims 1 to 7, characterized in that: The following steps are involved: An electrode slurry including a positive electrode active material is coated on at least one functional surface of a current collector, dried and rolled to form a precursor, and the precursor is placed in a closed container containing a mixed atmosphere and reacted for a period of time under a pressure of 0.1-0.3Mpa to obtain the positive electrode sheet; wherein, by volume, the mixed atmosphere includes water, carbon dioxide and oxygen in a molar ratio of 1-1.5:1-1.5:1-1.

5.

9. The preparation method according to claim 8, characterized in that: The internal temperature of the sealed container is 25°C-60°C.

10. A battery, characterized in that: The positive electrode sheet comprises any one of claims 1 to 7.

11. A battery pack, characterized in that: Comprising the battery as claimed in claim 10.

12. An electrical equipment, characterized in that: Comprising the battery according to claim 10 or the battery pack according to claim 11.

Citation Information

Patent Citations

  • Transition metal phosphate-clad composite lithium ion battery anode material

    CN101859887A

  • Coated active material, and lithium solid-state battery

    CN103534845A

  • Preparation method of lithium aluminate / lithium carbonate coated NCA cathode material

    CN111653747A

  • Lithium-ion battery positive pole piece and preparation method thereof

    CN112151807A

  • Coating method for retarding generation of internal cracks of material and product and application thereof

    CN115732688A